General banking activities of Janata Bank limited, a study on Brahmanbaria corporate branch, Brahmanbaria - Farezi, Al (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.